Inovasi Pelayanan dalam Penangulangan Kemiskinan Studi Kasus Pada Unit Pelayanan Terpadu Penanggula ngan Kemiskinan (UPTPK) di Kabupaten Sragen - Rohmah, USISA (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2016)
Capacity development in poverty reduction activities are crucial, based on the updated figures issued by BPS poverty levels have not been able to reduce poverty targeting accordingly, especially in poor areas. This paper aims to develop innovation and as a form of capacity building in poverty reduction, Sragen government initiated service innovation through Unit Pelayanan Terpadu Penanggulangan Kemiskinan (UPTPK). The research method is qualitative descriptive type. The results showed UPTPK implementation services based on criteria supported by the poverty report of (Tim Nasional Percepatan Penangulangan Kemiskinan) TNP2K and proverty report by PPLS (Pendataan Program Perlindungan Sosial) BPS 2011 to be better targeted distribution. UPTPK service innovation. Sragen in building a bureaucracy based management plurality, creativity, fairness, necessity, responsiveness to construct public service management appreciate the differences that can be accessed by different groups, so that justice can be upheld services. UPTPK services implementation are still having problems related to the budget, human resources personnel and the lack of support DPRD Sragen district. Keywords : Poverty, Innovation and Strategic Management of Public Services.